Small and medium-sized enterprise: prioritization of Internet bandwidth needs for business purposes - Abubakar Ibrahim, Adamu; Lawrence, Japhet Eke; Melmusi, Zerni; Haruna, Chiroma; Tarigan, Bahagia; Rohadi, Erfan; ., Mungad (SERSC Australia, 2018)
The use of internet bandwidth has become very important to the increasing number of small and medium-sized enterprise (SME). Regrettably, many employees are prone to abuse their unlimited internet access at work for non-work related purposes. Policies and monitoring of employee internet bandwidth use increase a firm’s productivity. Unfortunately, trust issues between a company and its employees significantly affect the latter’s organizational commitment and turnover intentions. This research proposes a model which allows employees to use their organization’s internet bandwidth at work for work as well as non-work purposes while at the same time effectively utilizing the internet bandwidth for work purposes. This paper presents a firm’s effective bandwidth utilization conceptual model which has been developed and tested statistically, and it also compares the resulting findings with the leading empirical studies in this domain.